Structural and Functional Divergence of Gonadotropin-Inhibitory Hormone (GnIH) from Jawless Fish to Mammals - Ogawa, Satoshi; Parhar, Ishwar (Frontiers in Endocrinology, 2014)
Gonadotropin-inhibitory hormone (GnIH) was discovered as a novel hypothalamic peptide that inhibits gonadotropin release in the quail. The presence of GnIH-homologous peptides and its receptors (GnIHRs) have been demonstrated in various vertebrate species including teleosts, suggesting that the GnIH-GnIHR family is evolutionarily conserved. In avian and mammalian brain, GnIH neurons are localised in the hypothalamic nuclei and their neural projections are widely distributed. GnIH acts on the pituitary and gonadotropin-releasing hormone (GnRH) neurons to inhibit reproductive functions by decreasing gonadotropin release and synthesis. In addition, GnIH-GnIHR signalling is regulated by various factors such as environmental cues and stress. However, the function of fish GnIH-orthologs remain inconclusive because the physiological properties of fish GnIH peptides are debatable. This review summarizes the current research progress in GnIH-GnIHR signalling and their physiological functions in vertebrates with special emphasis on non-mammalian vertebrate species.